2022
DOI: 10.1097/md.0000000000029715
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of immune checkpoint inhibitors in metastatic castration-resistant prostate cancer: A systematic review and meta-analysis

Abstract: Background: We aim to assess the efficacy and safety profiles of immune checkpoint inhibitors in patients with metastatic castration-resistant prostate cancer using a meta-analysis.Methods: We extracted and examined data from phase I, II and III clinical trials from PubMed, Embase, Web of Science, and Cochrane Library, which included patients with metastatic castration-resistant prostate cancer who were treated with immune checkpoint inhibitors. We performed a meta-analysis to investigate several indexes of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…cancer patients, respectively (83). Regarding PSAR, similar results were obtained; while the PSAR for Pembrolizumab monotherapy, Ipilimumab monotherapy, and Ipilimumab-plus-Nivolumab were 11%, 19%, and 14%, respectively in the mentioned study (83), it was 4.5%, 15.3%, and 13.6% for anti-PD-1/PD-L1 monotherapy, anti-CTLA-4 monotherapy, and anti-PD-1/PD-L1+anti-CTLA-4 regimen in accordance to our findings, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cancer patients, respectively (83). Regarding PSAR, similar results were obtained; while the PSAR for Pembrolizumab monotherapy, Ipilimumab monotherapy, and Ipilimumab-plus-Nivolumab were 11%, 19%, and 14%, respectively in the mentioned study (83), it was 4.5%, 15.3%, and 13.6% for anti-PD-1/PD-L1 monotherapy, anti-CTLA-4 monotherapy, and anti-PD-1/PD-L1+anti-CTLA-4 regimen in accordance to our findings, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…cancer patients, respectively (83). Regarding PSAR, similar results were obtained; while the PSAR for Pembrolizumab monotherapy, Ipilimumab monotherapy, and Ipilimumab-plus-Nivolumab were 11%, 19%, and 14%, respectively in the mentioned study (83), it was 4.5%, 15.3%, and 13.6% for anti-PD-1/PD-L1 monotherapy, anti-CTLA-4 monotherapy, and anti-PD-1/PD-L1+anti-CTLA-4 regimen in accordance to our findings, respectively. Although initial studies have proposed that immunotherapy with an autologous active cellular vaccine (Sipuleucel-T) provide promising outcomes for men with prostate cancer (84), the body of evidence came into the conclusion that prostate tumor is less immunogenic than thought before (85-87).…”
Section: Discussionmentioning
confidence: 99%
“…Only two of the 14 patients with advanced mCRPC in the first trial of anti-CTLA-4 antibodies for PCa demonstrated a decrease in prostate-specific antigen (PSA) ≤50%. Subsequently, a clinical study expanded the number of mCRPC patients to 71 to test the difference in efficacy of Ipilimumab and radiotherapy combined with Ipilimumab [26]. 16% of patients in the highest dose group had a decrease in PSA of ≤50%, six had no progression, and one sustained a response.…”
Section: Blocking Ctla-4 In Prostate Cancermentioning
confidence: 99%